SENSITIVITY, SAFETY, AND THE LAW: A REPLY TO PARDO. (September 2019) - Enoch, David; Spectre, Levi
ABSTRACT: In a recent paper, Michael Pardo argues that the epistemic property that is legally relevant is the one called Safety, rather than Sensitivity. In the process, he argues against our Sensitivity-related account of statistical evidence. Here we revisit these issues, partly in order to respond to Pardo, and partly in order to make general claims about legal epistemology. We clarify our account, we show how it adequately deals with counterexamples and other worries, we raise suspicions about Safety's value here, and we revisit our general skepticism about the role that epistemological considerations should play in determining legal policy.